The vices of economists, the virtues of the bourgeoisie - McCloskey, Deirdre N. (Amsterdam University Press, 1996)
Over the past fifty years, economists have fallen into three bad habits - three 'vices': bad statistics, bad theory, and bad applications of statistics and theory to public affairs. This book details the vices, tracing them to the influence of three giants of the 1940s and 1950s in economics, the Americans Lawrence Klein and Paul Samuelson, and the Dutchman Jan Tinbergen. McCloskey recommends a "bourgeois', even feminine, virtue to replace the aristocratic and masculine vices of modern economics. She sees intellectual life as a market, but a bourgeois market of negotiating equals, not the anonymous, peasant market of conventional economics.